2021
DOI: 10.1002/marc.202100299
|View full text |Cite
|
Sign up to set email alerts
|

Macrocyclic Photoinitiator Based on Prism[5]arene Matching LEDs Light with Low Migration

Abstract: In this work, a naphthalene-based macrocycle prism[5]arene (NP 5 OCH 3 ) is developed as a novel kind of photoinitiator. When NP 5 OCH 3 is irradiated under light, the bond between methylene and naphthalene can be quickly broken owning to the existence of ring tension. The macrocycle is cleaved to linear oligomer biradicals, which can effectively initiate the free radical photopolymerization of acrylate monomers. Compared with conventional photoinitiators, NP 5 OCH 3 has strong light absorption in the waveleng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…31−33 Second, the macrocyclic P6/NP5 exhibited a much lower migration rate and cytotoxicity than other small-molecule photosensitizers, owing to the absence of small molecular fragment generation. 34,35 In addition, the host−guest complex extended the initiating wavelength of Iod from ultrashort ultraviolet to nearultraviolet, which could better match the environment-friendly LED light source. In this way, it would be proven that the supraphotoinitiators with a nondiffusion-controlled photoelectron transfer process could be developed for highly efficient photopolymerization.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…31−33 Second, the macrocyclic P6/NP5 exhibited a much lower migration rate and cytotoxicity than other small-molecule photosensitizers, owing to the absence of small molecular fragment generation. 34,35 In addition, the host−guest complex extended the initiating wavelength of Iod from ultrashort ultraviolet to nearultraviolet, which could better match the environment-friendly LED light source. In this way, it would be proven that the supraphotoinitiators with a nondiffusion-controlled photoelectron transfer process could be developed for highly efficient photopolymerization.…”
mentioning
confidence: 99%
“…At the same time, the newly presented peaks (H a , H b , H c , and H d ) on the 1 H NMR spectra proved that P6 would be broken to a straight chain (P6OC2H5-α/β-chain), which had been studied in our previous work. 34,35 The characteristic peaks of iodobenzene and other photodegradation products recovered from the round and wideshaped peaks to sharp and narrow peaks showed that the photodegradation products were released from the cavity of macrocycles and escaped from the reaction cage. NP5-Iod was shown to undergo similar light reactions under light irradiation in Figure S12.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…18 As a result of these appealing properties, prismarenes have attracted significant interest in the scientific community over the last three years. [20][21][22][23][24][25][26] An intriguing aspect of prismarenes pertains to their chirality. Like pillararenes, [27][28][29] prism[n] arenes exhibit planar chirality (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Among various supramolecular host molecules, macrocyclic compounds embody excellent host–guest properties due to their specific cavity structures that endow them with efficient molecular recognition for different kinds of guests. 1 Prismarenes, 2–8 as one novel kind of macrocyclic host reported in 2020 by Gaeta and his colleagues, have one π-electron-rich aromatic cavity originating from the naphthalene ring repeating units. Structural features of prismarenes have afforded them outstanding properties to selectively complex with a variety of electron-deficient guests.…”
mentioning
confidence: 99%